(untitled) (Bangladesh Journal of Medicine, 2021)
Introduction: Based on preliminary surveys in this study, it was found 86.7% of respondents suffered from accute respiratory infection experienced 4 times reinfection within 3 months and 50% of respondents rarely consumed balanced nutritious food. Aims: to find the correlation between clean and healthy lifestyle behaviours, healthy housing and the frequency of accute respiratory infection in children under the age of 1-4 years. Method: a cross-sectional study was used by involving mothers or caregivers with infants aged 1-4 years in Malang Regency. A questionnaire was applied as research instrument. Result: Statistical analysis shows that there is a significant correlation between family members who smoke (p-value=0.021) and the level of home density (p-value=0.03) with the frequency of acute respiratory tract infections in toddlers. While the relationship of other variables such as the sex of children under five (p-value=0.799), clean and healthy lifestyle behaviour: delivery at primary health care (p-value=0.084), exclusive breastfeeding(p-value=0.940), routinely visiting Integrated Healthcare Center (p-value=0.396), hand washing behaviour (p-value=0.523), consuming healthy food (pvalue= 0.247), and infant’s activity(p-value=0.096), healthy housing: ventilation (p-value=0.396) and lighting (p-value=0.767) have no a significant correlation with incident of accute respiratory infection in infants . Conclusion: There is a correlation between family members who smoke and the level of home density with the frequency of accute respiratory infection in children under the age of 1-4 years Bangladesh J Medicine January 2021; 32(1) : 19-24